Integrating research and practice with a view to enhancing sports performance: examples from sprint acceleration - Bezodis, N. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
One of the three primary purposes of ISBS is to bridge the gap between researchers and practitioners. This paper aims to identify important concepts for incorporating coaching viewpoints into biomechanical analyses in an attempt to enhance sports performance. A continuum of possible sources of evidence was identified and, through a series of sprint acceleration-based examples, four key concepts were proposed. These were 1) the need for a clear and appropriate common goal to be defined, 2) the requirement for asking relevant questions, 3) the need to provide meaningful answers, and 4) the ability to demonstrate that a difference can be made. These concepts provide a framework to stimulate discussion amongst researchers and practitioners for how this integration of information, and ultimately levels of sporting performance, can continue to be improved.